Teachers’ Practices Toward Cultural Representations in an EFL Textbook: Preparing Students for A Global Experience - Novita, Dian; Yamin, Moh.; Taufiq, Wahyu; Dilna, Sema G. (Universitas Pendidikan Mandalika, 2024)
Acquiring a foreign language necessitates navigating practical situations that transcend linguistic and cultural barriers. Therefore, it is the teachers’ responsibility to develop these abilities. However, teachers rarely do so in a foreign language (FL) teaching. Integrating culture into the process of language teaching becomes crucial. Utilizing the textbook is one method to incorporate culture into the FL classroom, as it contains cultural material and linguistics. Limited research has been devoted to pedagogical analysis compared to the extensive concentration on content analysis in ELT textbook studies. The study aims to examine the teachers’ approaches to cultural depictions in an international English for Foreign Language (EFL) textbook, intending to educate students on a global worldview. The present study employed a qualitative research method with a case study design. The study recruited two junior high school English teachers who taught seventh-grade students at a private school in East Java, Indonesia. These teachers had incorporated cultural elements into their teaching. The instruments used to accomplish the research purpose were observation and post-observation interviews. The study's findings have verified that teachers utilized a comparative approach in presenting foreign cultural elements from the supplementary book to enhance English language learning. Exploring the students’ culture and contrasting it with foreign cultures has the potential to inspire greater participation from students in classroom activities. Using this strategy enables students to develop their English language proficiency in both linguistic and cultural aspects.